The dynamic proteome of Lyme disease Borrelia - Norris, Steven J (BioMed Central, 2006)
The proteome of the spirochete bacterium Borrelia burgdorferi, the tick-borne agent of Lyme disease, has been characterized by two different approaches using mass spectrometry, providing a launching point for future studies on the dramatic changes in protein expression that occur during transmission of the bacterium between ticks and mammals.